THE ROLE OF COLPOSCOPY IN THE DIAGNOSIS OF HPV-ASSOCIATED DISEASES OF THE CERVIX - Zaripova Sh.X. (Central Asian Journal of Medicine, 2025)
According to WHO recommendations (2020), a high-performance method of screening for cervical cancer is testing for the human papillomavirus (HPV) followed by colposcopy diagnostics. The aim of the study was to investigate the informativeness of the colposcopy method in the diagnosis of precancerous diseases of the cervix and early stages of cervical cancer in a group of HPV-positive women. The study included 400 (6.8%) HPV+ women who underwent colposcopy at the next stage. The coverage of colposcopy examination was 87.5%. The results of the histological examination showed the presence of CIN II in 32.1%, CIN III in 19.0%, CIS HPV in 5.1% and invasive cervical cancer in 2.6%. The colposcopy results were compared with the histological results, which showed the informativeness of colposcopy in 91.4%.